On complementary quadratic fractional programming problem - Abdulrahim, Basiya (International Journal of Applied Mathematical Research, 2014)
In this paper, a class of optimization problems has been considered where quadratic fractional programming problem has an additional characteristic, i.e Complementary quadratic fractional programming problem (CQFPP) and consequently a convergent algorithm has been developed in the following discussion. Numerical examples have been provided in support of the theory. By using Matlab 2011 version 7.12.0.635 (R2011a). Keywords: CQFPP, Solving CQFPP by new technique to modified simplex method.